The Problem of Representation of Religious in Contemporary Art. Secular and Postsecular Perspectives - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2017)
The article deals with the relationship between religion and contemporary art, discussing their configurations from two different perspectives – the one of secularization and the postsecular one. The author mantains that in the perspective of secularization the fields of religion and art are treated as autonomous and separate, therefore the passage to postsecular condition implicates the destruction of principle law of autonomy, by this opening the possibility of the interlaying of the contexts of religion and art. The article comes to the conclusion that postsecular approach supposes that the relationship between religion and contemporary art becomes possible only by accepting the refusal of the direct representation and this means that religious implications can be recognised not as the representations of religious contents, but rather as the track of them, which can assume the forms of profanation or reflection on the experience of secularization.
Keywords: religion; art; autonomy; secularization; profanation; postsecularity